Direct Decomposition Processing of Tritiated Methane by Helium RF Plasma. (3rd April 2017) - Katayama, Kazunari; Fukada, Satoshi
Abstract: With the aim of developing a method for the recovery of tritium from tritium-bearing hydrocarbons, it was shown experimentally that methane can be decomposed directly into hydrogen and carbon in RF plasmas via reactions initiated by electrons. Measurements performed with CH4 and CH3 T in a helium RF plasma indicate that the degree of decomposition of CH3 T is substantially smaller than that of CH4 . This is considered to be caused by a very low concentration of CH3 T. It was found that a majority of tritium dissociated from CH3 T is retained in the plasma reactor. However, a certain amount of retained tritium could be removed by a discharge-cleaning of oxygen.